Development Of Poly(Β-Cyclodextrin Functionalized Ionic Liquid) Conjugated Magnetic Nanoparticles As An Adsorbent For Microextraction Of Polycyclic Aromatic Hydrocarbons From Food Samples - Boon, Yih Hui (2020)
Food contamination is a global food safety issue which pose a health concern. Analysis of food contaminants is essential to ensure consumer safety and compliance with regulatory limits. Thus, development of simple, miniaturize, and sensitive sample preparation techniques are always a choice of interest. This study aims to develop and investigate new nanomaterial, namely poly(βCD-IL)@Fe3O4 and their applications in the microextraction of low and high molecular weight polycyclic aromatic hydrocarbons (PAHs) that have been listed as priority pollutants by European Community (EC) and Environmental Protection Agency (EPA). In the first part of study, poly(βCD-IL)@Fe3O4 was successfully synthesized and characterized by various techniques including FT-IR, CHN elemental analysis, XRD, TEM, SEM, VSM, BET, TGA, DSC, zeta potential and wettability measurement. Thereafter, poly(βCD-IL)@Fe3O4 was applied in magnetic μ-SPE technique as an adsorbent coupled with gas chromatographic-flame ionization detection (magnetic μSPE-GC-FID) for the determination of five selected low molecular weight PAHs in rice samples. Under optimized conditions, the calibration curves were linear for the concentration ranging between 0.1 and 500 μg kg-1 with coefficient of determination (R2) from 0.9970 to 0.9982 for all analytes. Detection limits (LODs) ranged at 0.01–0.18 μg kg-1 in real matrix. The RSD values ranged at 2.95%–5.34% (intra-day, n=6) and 4.37%–7.05% (inter-day, n=6). The sorbent showed satisfactory reproducibility in 2.9% to 9.9% range and acceptable recovery values at 80.4%–112.4% for the real samples.